2014
DOI: 10.1155/2014/769608
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Attenuates Endothelial Apoptosis Induced by Low Shear Stress via mTOR and Sestrin1 Related Redox Regulation

Abstract: Background. Studies indicate the dramatic reduction of shear stress (SS) within the rapamycin eluting stent (RES) segment of coronary arteries. It remains unclear about the role of rapamycin in endothelialization of stented arteries where SS becomes low. Since mTOR (mammalian target of rapamycin) pathway is involved in the antioxidative sestrins expression, we hypothesized that rapamycin attenuated low SS (LSS) induced endothelial dysfunction through mTOR and sestrin1 associated redox regulation. Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…As GIT2 possesses important roles in stress sensitivity ( 18 , 19 , 159 ), aging ( 13 ), and somatic energy management, this molecule potentially provides a novel target for therapies designed to interdict pathological aging and age-related disease. With respect to potential therapeutic exploitation of this keystone factor, our transcriptomic and proteomic analyses have demonstrated that GIT2 is strongly linked with multiple therapeutically tractable protein targets, e.g., glyoxylase 1 [Glo1: Figure 8 ( 160 163 )] and sestrin 1 [Sesn1: Figure 8 ; ( 82 , 92 , 164 , 165 )]. Considerable further experimentation will be clearly required to uncover the optimal therapeutic mechanisms of exploiting GIT2 expression for the remediation of age-related pathologies, however, at the present time, it represents an interesting new master-regulator of the neurometabolic aging process.…”
Section: Discussionmentioning
confidence: 99%
“…As GIT2 possesses important roles in stress sensitivity ( 18 , 19 , 159 ), aging ( 13 ), and somatic energy management, this molecule potentially provides a novel target for therapies designed to interdict pathological aging and age-related disease. With respect to potential therapeutic exploitation of this keystone factor, our transcriptomic and proteomic analyses have demonstrated that GIT2 is strongly linked with multiple therapeutically tractable protein targets, e.g., glyoxylase 1 [Glo1: Figure 8 ( 160 163 )] and sestrin 1 [Sesn1: Figure 8 ; ( 82 , 92 , 164 , 165 )]. Considerable further experimentation will be clearly required to uncover the optimal therapeutic mechanisms of exploiting GIT2 expression for the remediation of age-related pathologies, however, at the present time, it represents an interesting new master-regulator of the neurometabolic aging process.…”
Section: Discussionmentioning
confidence: 99%
“…The parallel flow chamber designed by the Shanghai Medical Instrument School was previously described (Zhang et al , 2014). Briefly, cells were grown to confluence on a coverslip and placed in the chamber, which was established by sandwiching a silicon gasket between two stainless steel plates with a coverslip sink in the base plate.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with other studies, we successfully knocked down the expression of Raptor by siRNA in SKOV3 cells. 31 , 32 Moreover, the phosphorylation of mTOR and S6K1 was decreased. However, the expression of Raptor was partially downregulated by siRNA.…”
Section: Discussionmentioning
confidence: 98%